Pengaruh Perbandingan Tepung Talas Beneng (Xanthosoma undipesh K. Koch) dan Tepung Kacang Merah (Phaseolus vulgaris L.) terhadap Karakteristik Flakes - Cahyaningtyas, I Gusti Ayu Putu Prabawati; Putra, I Nengah Kencana; Wiadnyani, Anak Agung Istri Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 3 (2024): Jurnal ITEPA, 2024)
Flakes are a convenient instant cereal that is typically served with the addition of milk, providing a nutritional boost. Traditionally, flakes on the market are made from wheat and corn. However, there has been a recent development in producing flakes using local food ingredients such as tubers and nuts. This study focuses on utilizing beneng taro and red beans in making flakes, aiming to promote local food utilization and enhance the characteristics and nutritional value of the product. The research seeks to investigate the impact of the ratio of beneng taro flour to red bean flour on various characteristics of flakes and to determine the optimal ratio for achieving the best flake characteristics. The research design employed in this study was a Completely Randomized Design (CRD) with five treatment levels: ratios of beneng taro flour to red bean flour at 90:10, 80:20, 70:30, 60:40, and 50:50. Each treatment was replicated three times, resulting in a total of 15 experimental units. Data obtained from the experiments were subjected to variance analysis, and if a significant effect was observed, the Duncan Multiple Range Test (DMRT) was performed. The research findings indicated that the ratio of beneng taro flour to red bean flour significantly influenced various characteristics of flakes, including water content, ash content, fat content, protein content, carbohydrate content, crude fiber content, crunchy resistance in milk, and texture parameters such as hardness. Additionally, it had a significant impact on hedonic characteristics, specifically color, aroma, taste, and overall acceptability. The most favorable treatment identified was a ratio of 60% beneng taro flour to 40% red bean flour, meeting specific criteria: water content 2.29%, ash content 3.64%, fat content 9.73%, protein content 12.73%, carbohydrate content 71.62%, crude fiber content 3.96%, hardness 20.69N, crisp resistance in milk 4.27 minutes, and favorable hedonic ratings for color, aroma, texture, taste, and overall acceptability. Keywords : Flakes , beneng taro flour, red bean flour